Bell hooks's Legacy and Social Work: A Distillation of Her Key Ideas about Love and Some Implications for Social Work Practice. (7th July 2022) - Ross, Dyann
Abstract: bell hooks is regarded as one of the most influential cultural critics, writers and speakers of the last fifty years. She has published more than forty books which collectively articulate a feminist critique of white supremacy, capitalism and patriarchy. At the same time, she offers a loving, non-violent and just vision for attaining collective and personal well-being. Hooks makes feminist theory meaningful as a guide not only for Black American women but also for anyone seeking to resist inequality and discrimination due to race, class and gender. Her main thesis is that where there is love there can be no oppression. hooks's contribution is traced through some of the key themes of her books which explicitly refer to love to develop a rich understanding of love and its transformative power. These contributions are then considered for the relevance they have for social work. Social workers can practice love by fostering their own and others': self-love; willingness to learn; and cultural responsiveness. Two loving practices with other people are dadirri (deep listening) and narrative resistance. Love provides the power to do the justice and healing work. Abstract : bell hooks was an internationally acclaimed Black feminist cultural critic, intellectual dissident and writer whose influence in social work is building but deserves more attention. Her main ideas of relevance for social work are: Love is the willingness to learn and change ourselves and to enable others to change through de-colonising our minds and hearts for personal divestment of privilege and collective well-being and justice. Where there is love there is no oppression, and love-informed actions can resist, challenge and transform oppression. Black and Aboriginal ideas and ways can guide social workers in practising self-love, love for others and nature, and involves dadirri—deeply listening to and being with people, animals and nature, cultural responsiveness and resistance against oppressive narratives.